2023
DOI: 10.2147/dmso.s409983
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Six Insulin Resistance Surrogates and Nonalcoholic Fatty Liver Disease Among Older Adults: A Cross-Sectional Study

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) represents a large and growing public health problem. Insulin resistance (IR) plays a crucial role in the pathogenesis of NAFLD. The aim of this study was to determine the association of triglyceride-glucose (TyG) index, TyG index with body mass index (TyG-BMI), lipid accumulation product (LAP), visceral adiposity index (VAI), triglycerides/high-density lipoprotein cholesterol ratio (TG/HDL-c) and metabolic score for IR (METS-IR) with NAFLD in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…The predictive efficacy of TG/HDL‐c (AUC = 0.674) was found to be superior to that of TyG (AUC = 0.616) and TyG‐BMI (AUC = 0.633), as depicted in Figure 2. Contrary to our findings, in studies of benign diseases, TyG‐BMI and TyG showed superior efficacy in evaluating IR than TG/HDL‐c 27,28 . We speculated that cholesterol metabolism may affect the progression of PC, as IR results in elevated triglyceride levels and decreased HDL‐c levels 46 .…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The predictive efficacy of TG/HDL‐c (AUC = 0.674) was found to be superior to that of TyG (AUC = 0.616) and TyG‐BMI (AUC = 0.633), as depicted in Figure 2. Contrary to our findings, in studies of benign diseases, TyG‐BMI and TyG showed superior efficacy in evaluating IR than TG/HDL‐c 27,28 . We speculated that cholesterol metabolism may affect the progression of PC, as IR results in elevated triglyceride levels and decreased HDL‐c levels 46 .…”
Section: Discussioncontrasting
confidence: 98%
“…Insulin resistance plays a crucial role in the pathophysiology of diabetes mellitus and causes a variety of metabolic disorders such as hyperglycemia, hyperinsulinemia, dyslipidemia and visceral obesity 16,26,28,39,40 . Currently, the homeostatic model assessment of IR and the hyperinsulinemic euglycemic clamp are accurate methods for assessing IR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies supported the close association between TyG-BMI index and visceral adiposity [ 26 ], type 2 DM [ 27 ], and metabolic syndrome [ 28 ]. The clinical value of TyG-BMI index on predicting occurrence of hypertension [ 29 ], nonalcoholic fatty liver disease [ 30 ], DM [ 31 ], and severe coronary artery disease [ 32 ] have been demonstrated in previous studies. Apart from the substantial correlation with various illness, TyG-BMI index was also useful for predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%